Pembelajaran Bahasa Jepang Perhotelan III Berbasis Daring di Masa Pandemi Covid-19 - Wijayanti, Anak Agung Ratih; Putranto, Isa Wahjoedi Dwi (Universitas Negeri Semarang, 2021)
This study aims to determine the learning process of Japanese Language Hospitality during the Pandemic Covid-19 period. This study was researching effectiveness of the online distance learning process and evaluate the weakness and problem occurred during learning process. This research was conducted on 43 students of the Faculty of Tourism at Triatma Mulya University Diploma IV Hospitality Program in Third Semester, Academic Year 2020/2021. The respondent was choosen from students who have learned Japanese Language Hospitality 3 on one semester from June to December 2020. The data collection method in this study used documentation techniques and questionnaires via google form. The online-based learning process carried out in this study is to create virtual classroom learning situations through online-based e-learning methods. Students not only listeners in class, but students are strongly directed to presentation about hotel hospitality using Japanese Language. The problem during learning process of Japanese Hospitality online are, the lack of supporting facilities in online class, less concentration and other distractions.